Implementation of the online learning process for students of UIN Imam Bonjol Padang - N. Nadhilah; R. Rusman (Universitas Pendidikan Indonesia, 2024)
Online learning is a new form of learning that can be carried out by students in line with current technological developments. This research aims to dig deeper into the implementation of the online learning process among UIN Imam Bonjol Padang students. The method used is descriptive with a qualitative approach. The results obtained from this research are the need to plan online learning before using it in a learning activity. The lecturer's plan to conduct online learning can have an impact on how effectively the plan is implemented. UIN Imam Bonjol Padang students use group study tactics to complete the online learning they have to carry out. In implementing online learning, various types of media are also needed for various aspects of material during online learning to support the learning process with access to the library. A structured implementation of online learning will create an ideal process for implementing education, making it easier for students to follow the learning process.